ENSO and Dengue, in the Pacifico Central and Huetar Atlántico Regions, Costa Rica, 1990 to 2011 - Ramirez Solano, Ana Maria; Chamizo Garcia, Horacio Alejandro; Fallas Sojo, Juan Carlos (Población y Salud en Mesoamérica, 2017)
Over the last years in Costa Rica, there has been a worrying increase in the number of people infected by Dengue. This situation reveals the necessity of searching for the causes that promote the mosquito’s proliferation; especially concerning the relationship with environmental type that affects life cycle of the vector, such as atmospheric phenomena: El Niño/Southern Oscillation (ENSO). Objective: The investigation objective was to analyze the effect that ENOS has in the propagation of the Dengue virus in Pacífico Central and Huetar Atlántico in Costa Rica between 1990 and 2011. Methods: It was used an experimental, ecological study and different sources like Ministerio de Salud (MINSA), the Instituto Meteorológico Nacional (IMN) and the Instituto Nacional de Estadística y Censos (INEC) as primarily information bases. Results: The monthly impact accumulated of Dengue grew up during the Warm Phase at the Pacífico, and it decreased at The Caribe, while during the Cold Phase the monthly impact accumulated expanded at The Caribe and detracted at the Pacífico. Conclusions: Among the numerous findings, it turns out that the ENSO phenomenon alters the percentage of the people infected at the littorals in an inverse way.